AN ANALYSIS OF DERIVATIONAL MORPHEMES IN THE FOUR POEMS ENTITLED “STILL I RISE”, “A BRAVE AND STARTLING TRUTH”, “MOTHER, A CRADLE TO HOLD ME” AND “A PLAGUED JOURNEY” BY MAYA ANGELOU - Bela Alpina Meindaningsih; Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
The title of the research is An Analysis of Derivational Morphemes in the Four Poems Entitled “Still I Rise," “A Brave and Startling Truth," “Mother, a Cradle to Hold Me,” and “A Plagued Journey” by Maya Angelou. The aims of this research are not only to identify what types of derivational morphemes are used but also to analyze which types of derivational morphemes are dominant in the four poems by Maya Angelou. The main theory used by Yule (2023) discusses morphology. In this research, the researcher used a descriptive-qualitative method. The data collection is taken from 4 poems by Maya Angelou titled "Still I Rise," “A Brave and Startling Truth," “Mother, a Cradle to Hold Me,” and “A Plagued Journey.". The data are identified, classified, and counted numerical data on derivational morphemes of words found in the four poems by Maya Angelou. The research results show that there are two types of derivational morphemes used in the four poems by Maya Angelou, namely prefixes and suffixes, which appear to have a total of 60 data points. The dominant types of derivational morphemes found in the four poems by Maya Angelou are the suffixes found in 52 data with a percentage of 86.7%.